The Challenges Traditional Banking Faces in the Era of Digitalization : The Case of the Czech Republic - Onuferová, Michaela; Loužek, Marek, 1975-; Bednář, Milan, 1991-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
The diploma thesis responds to an increasing trend of digitalization of financial services. The globalized world is adopting new, quickly diffused technologies with an increasing speed, with the commercialization of the Internet in the 1990s being the primary reason for turbulent changes in many sectors of the economy. Banking, a sector with strict regulation and high barriers to entry, is currently facing the competition of small, agile companies that disrupt the market by combining technology and financial services – the FinTech. Their customer-centricity, convenient user experience and online-only approach have resulted in the growing popularity of the services (such as crowdfunding or peer-to-peer lending) and significant global investments into the new entrants. Furthermore, a shift in customer behaviour is noticeable, turning the previous banks’ dominance in the customer-bank relationship around. The aim of the thesis is to accurately describe these trends on the case of the Czech Republic. The core of the thesis is the statistical evaluation of online questionnaires aimed at the respondents’ approach to the incumbents and the new entrants, finding out that especially Millennials and capital city residents are less loyal to their banks and more willing to try the new possibilities in financial services, with almost a third of respondents already using them. The questionnaire is complemented by case studies of three successful FinTech companies (Fundlift, Twisto, Zonky) and an overview of the key indicators predetermining the possible success of the FinTech in the Czech Republic.Finally, the author discusses the strengths and weaknesses of banks and the FinTech and their future coexistence on the market.
Vedoucí práce: Marek Loužek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses